Effective method of measuring the radioactivity of [ 131I]‐capsule prior to radioiodine therapy with significant reduction of the radiation exposure to the medical staff. (8th July 2016) - Lützen, Ulf; Zhao, Yi; Marx, Marlies; Imme, Thea; Assam, Isong; Siebert, Frank‐Andre; Culman, Juraj; Zuhayra, Maaz
Abstract : Radiation Protection in Radiology, Nuclear Medicine and Radio Oncology is of the utmost importance. Radioiodine therapy is a frequently used and effective method for the treatment of thyroid disease. Prior to each therapy the radioactivity of the [   131 I ] ‐capsule must be determined to prevent misadministration. This leads to a significant radiation exposure to the staff. We describe an alternative method, allowing a considerable reduction of the radiation exposure. Two [   131 I ] ‐capsules ( A 01 = 2818.5 ;   A 02 = 73.55.0   MBq ) were measured multiple times in their own delivery lead containers — that is to say, [   131 I ] ‐capsules remain inside the containers during the measurements (shielded measurement) using a dose calibrator and a well‐type and a thyroid uptake probe. The results of the shielded measurements were correlated linearly with the [   131 I ] ‐capsules radioactivity to create calibration curves for the used devices. Additional radioactivity measurements of 50 [   131 I ] ‐capsules of different radioactivities were done to validate the shielded measuring method. The personal skin dose rate ( H P ( 0.07 ) ) was determined using calibrated thermo luminescent dosimeters. The determination coefficients for the calibration curves were R 2 > 0.9980 for all devices. The relative uncertainty of the shielded measurement was < 6.8 % . At a distance of 10 cm from the unshielded capsule the H P ( 0.07 ) was 46.18   μ Sv / ( GBq ⋅ s ), and on the surface of the lead container containing the [   131 I ] ‐capsule the H P ( 0.07 ) was 2.99 and 0.27   μ Sv / ( GBq ⋅ s ) for the two used container sizes. The calculated reduction of the effective dose by using the shielded measuring method was, depending on the used container size, 74.0% and 97.4%, compared to the measurement of the unshielded [   131 I ] ‐capsule using a dose calibrator. The measured reduction of the effective radiation dose in the practice was 56.6% and 94.9 for size I and size II containers. The shielded [   131 I ] ‐capsule measurement reduces the radiation exposure to the staff significantly and offers the same accuracy of the unshielded measurement in the same amount of time. In order to maintain the consistency of the measuring method, monthly tests have to be done by measuring a [   131 I ] ‐capsule with known radioactivity. PACS number(s): 93.85.Np, 92.20.Td, 87.50.yk, 87.53.Bn